PENERAPAN INTEGRATED MARKETING COMMUNICATION BUMDES SINERGI SIDOWAYAH DALAM PENGELOLAAN DESA WISATA SIDOWAYAH PERIODE 2023 - Azizah, Fatimah Nur; Wangi, Maya Sekar; Maserona, Lukas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Sidowayah Village, located in Klaten Regency, Central Java, has significant potential in the tourism sector, particularly through water attractions like Umbul Siblarak. The Covid-19 pandemic that began in 2020 led to a sharp decline in visitor numbers. Bumdes Sinergi Sidowayah responded to this challenge by implementing an Integrated Marketing Communication (IMC) strategy in 2023 to increase tourist numbers and strengthen the positive image of Umbul Siblarak. This research aims to analyze the effectiveness of IMC implementation by Bumdes in managing Sidowayah Tourism Village. Five key IMC elements, namely advertising, sales promotion, public relations, direct marketing, and personal selling, are examined in depth. The research employs a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentation. The results indicate that IMC implementation successfully increased visitor numbers and reinforced Umbul Siblarak’s image as a safe and attractive tourist destination. Keywords: Integrated Marketing Communication, Bumdes Sinergi Sidowayah, Umbul Siblarak, Marketing, Tourism